2010
DOI: 10.1258/acb.2010.090290
|View full text |Cite
|
Sign up to set email alerts
|

Increases in urinary creatinine and blood pressure during early pregnancy in pre-eclampsia

Abstract: Background: It is important to predict the development of pre-eclampsia (PE) during early pregnancy to prevent its occurrence later on. In this study, we studied urinary biochemical parameters and blood pressure (BP) during and after pregnancy to find useful parameters for predicting PE. Methods: A case-control study was performed in 25 PE patients and 172 normotensive pregnant women. Twelve biochemical parameters were measured in spot urine, and the systolic and diastolic BPs were measured using an automated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, many of the metabolites were not the same as those highlighted here, including the hippurate to creatinine ratio, which might be attributed to the difference in gestational age between the studies resulting in changing metabolic profiles [ 24 ]. Non-metabolomics methods have been used to predict preeclampsia from urine samples, focusing on urinary albumin to creatinine ratios as a measure of kidney function [ 25 ], and creatinine levels in urine [ 26 ]. Increased urinary creatinine was found to be predictive of preeclampsia in a study as early as 8–10 weeks gestation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many of the metabolites were not the same as those highlighted here, including the hippurate to creatinine ratio, which might be attributed to the difference in gestational age between the studies resulting in changing metabolic profiles [ 24 ]. Non-metabolomics methods have been used to predict preeclampsia from urine samples, focusing on urinary albumin to creatinine ratios as a measure of kidney function [ 25 ], and creatinine levels in urine [ 26 ]. Increased urinary creatinine was found to be predictive of preeclampsia in a study as early as 8–10 weeks gestation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-metabolomics methods have been used to predict preeclampsia from urine samples, focusing on urinary albumin to creatinine ratios as a measure of kidney function [ 25 ], and creatinine levels in urine [ 26 ]. Increased urinary creatinine was found to be predictive of preeclampsia in a study as early as 8–10 weeks gestation [ 26 ]. Our corresponding findings of increased creatinine in urine may be an effect of the increased BMI and MAP of the women who developed preeclampsia and gestational hypertension [ 26 ], or possibly a marker of early renal involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 15 It has also been reported that renal function is highly correlated with SBP and DBP in women who develop HDP and that the combination of urinary creatinine (Cr) and SBP in early pregnancy can be considered a predictor of PE. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%